Digital marketing vs. conventional marketing: Preference of students who are residing in the Dhaka City - Hassan, Md. Khairul (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.